OC-028 Statin use is Associated with Improved Survival in Patients with Oesophageal Cancer: a Survival Analysis using the UK General Practice Research Database and National Cancer Registry. (4th June 2013) - Alexandre, L; Clark, A; Bhutta, H; Lewis, M P; Holt, S; Hart, A R
Abstract : Introduction: Patients with oesophageal cancer (OC) commonly present with an advanced stage of disease, and are often only amenable to palliative therapies. Of the minority suitable for potentially curative surgery, up to 50% develop recurrence at one year. Statins demonstrate several anticarcinogenic properties in oesophageal adenocarcinoma (OAC) cell lines including reducing cell proliferation, stimulating apoptosis and potentially limiting metastatic potential. We investigated for the first time the hypothesis that statin use after diagnosis or post-oesophagectomy was associated with improved survival in patients with OC. Methods: Cases of OC diagnosed between 1st January 2000 and 31st December 2009 were identified from the UK General Practice Research Database (GPRD). The GPRD data was linked to the UK National Cancer Registry (NCR) to determine histological subtype. Cox proportional hazard regression analysis with time-dependent exposures, estimated the associations between statin use (versus non-users) from diagnosis and post-surgery on overall survival and disease-specific survival. Multivariate analyses were adjusted for age, gender, body mass index, diabetes mellitus, cardiovascular disease, oesophagectomy, chemotherapy, radiotherapy and ACE inhibitor use. Results: In total 4445 cases of OC were identified, of which 606 were OAC and 344 were OSCC (histology data was available for 21.4% of patients). Overall 585 (13.2%) patients underwent oesophagectomy. In total 609 (13.7%) of patients were statin users following diagnosis and 109 (19.2%) following surgery. There were improved survival times following diagnosis for patients prescribed a statin with OC overall (HR = 0.71, 95% CI = 0.64–0.79, p < 0.001) and specifically OAC (HR = 0.58, 95% CI = 0.43–0.78, p < 0.001). Furthermore, statin use post-oesophagectomy was associated with improved survival in those with OC overall (HR = 0.66, 95% CI = 0.48–0.91, p = 0.013) and those with OAC specifically (HR = 0.58, 95% CI = 0.30–1.10, p = 0.096) with borderline significance. There were no significant effects between statin use and survival in patients with OSCC. Associations between statin use and overall survival were very similar to their effect on disease-specific survival. Conclusion: Statin use in patients with OC either after diagnosis or post-oesophagectomy is associated with improved survival. This data suggests a need for randomised controlled trials of statins in patients with OC. Disclosure of Interest: None Declared